The Effect of Digital Recruitment Platform and Accessibility on the Recruitment and Selection Effectiveness at a State-Owned Bank in North Sumatra - R. Meutia Fransiska; Fitri Dwiana; Johan Manurung; Ritha F. Dalimunthe (West Science Business and Management, 2024)
This study examines the effect of digital recruitment platforms and accessibility on recruitment and selection effectiveness at a state-owned bank in North Sumatra. This quantitative research employed simple random sampling to obtain 100 job applicants as respondents from a population of 308 applicants across 14 branch offices. Data collection utilized closed questionnaires, unstructured interviews, and documentation. Multiple linear regression analysis revealed that digital recruitment platforms and accessibility simultaneously influence recruitment effectiveness (F = 129.612, p < 0.001). Partially, digital recruitment platforms significantly influence recruitment effectiveness (β = 0.826, t = 15.357, p < 0.001), while accessibility shows a smaller but significant effect (β = 0.111, t = 2.065, p < 0.05). The regression model explains 72.2% of the variance in recruitment effectiveness (Adjusted R² = 0.722). This study demonstrates the crucial role of digital platforms in enhancing recruitment effectiveness in the banking sector, particularly for state-owned banks adapting to digital transformation